Contrastive analysis of physical development perameters registered in long-time training for sweep rowers - Braniste, G. (Cross-border research, 2023)
The management of the training process in sports is closely related to the awareness of the tight connection between performance and the morphological, functional, and psychological characteristics of the athlete. Achieving top results in Olympic events is highly influenced, on the one hand, by the genetically determined characteristics and, on the other hand, by the morphological, functional, and motor abilities developed by the athlete during his training. Considering the importance of properly understanding the evolutionary specificity of athletes in their pursuit to assess top competitive potential, this study provides a comparative analysis of the parameters that characterise the growth and development of the level of adaptation for sweep rowers, considering the growth interval between 12 and 20 years. The study established that, during the multi-annual training process, the bodies of the targeted athletes register significant adaptive changes in their morphological, functional, psychomotor, and sports-technicality parameters. As a result of the influence of either specific or non-specific physical efforts, there is an increase in the adaptability of the body while transferring to a much higher level of functionality within the registered parameters with useful and economical adaptive reactions influenced by environmental factors, be they internal or external. The research was carried out for seven years on a target group of 28 athletes and followed their evolution and specific parameters according to each age stage. In order to determine the rowers` degree of physical, morpho-functional, psychomotor development, and technical training, the screening data were applied at the State University of Physical Education and Sports in the Republic of Moldova. The research followed to register and evaluate measurements and rations of their waist circumference - in the standing and sitting position -, arm span, weight, chest perimeter, vital capacity of the lungs, with the subsequent determination of the vital index (tolerance level to oxygen deficiency in venous blood in Stange and Genchi breathtaking tests that characterise the level of oxygen saturation), absolute and relative strength of the hand and back, calculation of body mass and morphological maturity indices (Kettle index), body surface area (body gait), psychomotor tests (Romberg test), finger test-tapping 10 sec, reaction to a moving object, visual and auditory-motor reaction, recording of technical parameters of paddling on a competitive distance of 200 m. At the end of the study, we could understand and predict the peaks of the athletes` performance in association with the genetically determined characteristics of the body and favouring adaptive reactions to energy saving, as well as morpho-functional changes influenced by internal and external environmental factors. The importance of the results obtained at the end of the study was positively reflected in following the maximum level of training for their large-scale competitions such as the Olympic Games.